Strategi Adaptasi Coffee Shop terhadap Perubahan Perilaku Konsumen Anak Muda di Pangkalpinang - Olivia Anjelina; Silvi Dwi Ananda; Triyana Dinanti; Indah Noviyanti (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to describe how coffee shop entrepreneurs in Pangkalpinang adapt their operational strategies in response to changing consumer behavior among young people. Using a qualitative approach and interviews with coffee shop owners and customers, the research reveals that comfort, aesthetic interior design, and facilities such as Wi-Fi and power outlets are key factors in attracting Gen Z consumers. Moreover, social media plays a crucial role in influencing visit decisions and building customer loyalty. In facing challenges such as limited capital and maintaining product consistency, coffee shop owners implement innovations through menu updates, spatial redesign, improved service, and digital marketing strategies. This study highlights the importance of understanding digital lifestyles, community engagement, and responsiveness to trends in sustaining competitiveness in a rapidly evolving market.